Lenkung und Ablenkung - Honegger, Serge Brian (Schwabe Verlag, 2019)
This book is on four plays by John von Düffel, Peter Handke, and Franz Xaver Kroetz. The texts show a new understanding of direction and leadership, which is no longer related to hierarchical structured principles of organisation and to determining conceptions of planning and controlling.